Farmers’ grain storage and losses in Ethiopia: Measures and associates - Bachewe, Fantu Nisrane; Minten, Bart; Taffesse, Alemayehu Seyoum; Pauw, Karl; Cameron, Alethia; Genye, Tirsit (De Gruyter, 2020)
While storage losses at the farm are often assumed to be an important contributor to presumed large postharvest losses in developing countries, reliable and representative data on these losses are often lacking. We study farmers’ storage decisions and self-reported storage losses for grains based on two large-scale household surveys conducted in major agricultural areas in Ethiopia. We show that a relatively large share of grain production is stored by farm households for own consumption and that storage technologies are rudimentary. Farmers’ self-reported storage losses amount to an average of 4 % of all grains stored and 2 % of total harvest. These storage losses differ significantly by socioeconomic variables and wealth, as well as by crop and humidity. We further see strong spatial heterogeneity in storage losses being significantly higher in southwest Ethiopia. Efforts to scale up the adoption of improved storage technologies to reduce storage losses at the farm level should consider these characteristics.